IMPLEMENTATION OF PERSONAL HYGIENE KITCHEN CREW ON FOOD AND BEVERAGE PRODUCTS AT LABERSA TOBA HOTEL AND CONVENTION CENTER BALIGE - Indah Suryani Fajari N; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Apart from having to have good food quality, the application of hygiene in the field of food and beverage products must of course be applied to kitchen employees. Personal hygiene for good workers is one of the important things needed to keep food products safe from bacterial contamination. In this study, researchers used a qualitative descriptive method. The research subjects in this study were all Food and Beverage Product employees, totaling 20 people consisting of: Executive Chef, Jr. Sous Chef, Demi Chef, Chef De Partie, Cook, and Cook Helper who are involved in and related to procedures for implementing personal hygiene kitchen crew for Food and Beverage Products at Labersa Toba Hotel and Convention Center Balige. Then, the method of data collection is Observation, Interview, and Documentation. The results showed that the Implementation of Kitchen Crew Personal Hygiene in Food and Beverage Products at the Labersa Toba Hotel and Convention Center Balige had been implemented quite well and was in accordance with the Standard Operating Procedures that had been made by the hotel. However, there are still a number of Kitchen Crews who have not complied with and implemented the Standard Operating Procedures that have been made by the Hotel as they should. Keywords : Personal Hygiene, Food and Beverage Products, Kitchen Crew